2012
DOI: 10.1371/journal.pone.0039212
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Brain-Derived Neurotrophic Factor Levels Predict the Clinical Outcome of Depression Treatment in a Naturalistic Study

Abstract: Remission is the primary goal of treatment for major depressive disorder (MDD). However, some patients do not respond to treatment. The main purpose of this study was to determine whether brain-derived neurotrophic factor (BDNF) levels are correlated with treatment outcomes. In a naturalistic study, we assessed whether plasma BDNF levels were correlated with clinical outcomes by measuring plasma BDNF in patients with depressive syndrome (MADRS score ≥18), and subsequently comparing levels between the subgroup … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
40
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(45 citation statements)
references
References 28 publications
4
40
0
1
Order By: Relevance
“…Plasma BDNF levels were negatively correlated to MADRS scores following ketamine infusion but not midazolam, an active control, in another sample of treatment resistant MDD (Haile et al, 2014). This finding has previously been observed in MDD patients on standard antidepressants (Kurita et al, 2012) but another ketamine study did not observe changes in BDNF (Machado-Vieira et al, 2009b). Increased BDNF function may be explained by the results of a recent study which demonstrated that MDD patients with Val/Val BDNF allele at rs6265 (Val66Met single nucleotide polymorphism) exhibited increased antidepressant response to ketamine (Laje et al, 2012).…”
Section: Biomarkers Of Response To Ketaminesupporting
confidence: 76%
“…Plasma BDNF levels were negatively correlated to MADRS scores following ketamine infusion but not midazolam, an active control, in another sample of treatment resistant MDD (Haile et al, 2014). This finding has previously been observed in MDD patients on standard antidepressants (Kurita et al, 2012) but another ketamine study did not observe changes in BDNF (Machado-Vieira et al, 2009b). Increased BDNF function may be explained by the results of a recent study which demonstrated that MDD patients with Val/Val BDNF allele at rs6265 (Val66Met single nucleotide polymorphism) exhibited increased antidepressant response to ketamine (Laje et al, 2012).…”
Section: Biomarkers Of Response To Ketaminesupporting
confidence: 76%
“…In this context, BDNF baseline levels were not predictors of antidepressant response either, as observed in some pharmacological studies (Kurita et al, 2012; Tadic et al, 2011; Wolkowitz et al, 2011) but not in all (Umene-Nakano et al, 2010). Nonetheless, although BDNF meta-analyses supported the notion that depression improvement is associated with BDNF increasing, virtually all BDNF trials were not controlled; therefore it was not possible to disentangle antidepressant treatment effects from time effects and also from drug effects in platelets that store BDNF in the blood.…”
Section: Discussionmentioning
confidence: 71%
“…In some studies, BDNF is used as a biological marker of clinical conditions such as anxiety, depression, fibromyalgia, and schizophrenia (Kurita et al, 2012;Nurjono et al, 2012). However, the relationship between BDNF levels and anxiety disorders is controversial: BDNF levels appear to be either reduced increased, or not significantly altered in patients with anxiety disorders (Bonne et al, 2011;Dell'Osso et al, 2009;Dos Santos et al, 2011;Molendijk et al, 2012;Wang et al, 2011).…”
Section: Discussionmentioning
confidence: 99%